bHLH transcription factor bHLH115 regulates iron homeostasis in Arabidopsis thaliana - Liang, Gang; Zhang, Huimin; Li, Xiaoli; Ai, Qin; Yu, Diqiu (Journal of experimental botany, 2017)
Iron (Fe) deficiency is a limiting factor for the normal growth and development of plants, and many species have evolved sophisticated systems for adaptation to Fe-deficient environments. It is still unclear how plants sense Fe status and coordinate the expression of genes responsive to Fe deficiency. In this study, we show that the bHLH transcription factor bHLH115 is a positive regulator of the Fe-deficiency response. Loss-of-function of bHLH115 causes strong Fe-deficiency symptoms and alleviates expression of genes responsive to Fe deficiency, whereas its overexpression causes the opposite effect. Chromatin immunoprecipitation assays confirmed that bHLH115 binds to the promoters of the Fe-deficiency-responsive genes bHLH38/39/100/101 and POPEYE (PYE), which suggests redundant molecular functions with bHLH34, bHLH104, and bHLH105. This is further supported by the fact that the bhlh115-1 mutant was complemented by overexpression of any of bHLH34, bHLH104, bHLH105, and bHLH115. Further investigations determined that bHLH115 could interact with itself and with bHLH34, bHLH104, and bHLH105. Their differential tissue-specific expression patterns and the severe Fe deficiency symptoms of multiple mutants supported their non-redundant biological functions. Genetic analysis revealed that bHLH115 is negatively regulated by BRUTUS (BTS), an E3 ligase that can interact with bHLH115. Thus, bHLH115 plays key roles in the maintenance of Fe homeostasis in Arabidopsis thaliana.